دور اللغة العربية في التعليم الإسلامي لمواجهة الثورة الصناعية 4.0 - Wafa, Rimayul (Faculty of Education and Teachers Training of UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
With the presence of the Industrial Revolution 4.0, it automatically influenced the process of scientific development in Islamic education and Arabic. the development is felt in the aspects of its objectives, teaching methodology, and learning media, and competency standards of graduates who have soft skills and hard skills. Arabic, which has always been considered less important for some learners, has become an